Survival of Expiratory Aerosols in a Room: Study Using a Bi-compartment and Bi-component Indoor Air Model - Sreekanth Bathula; Srinivasan Anand; Thaseem Thajudeen; Yelia Shankaranarayana Mayya; Probal Chaudhury; Chaturvedi Shashank (Aerosol and Air Quality Research)
Abstract Recent studies argue that inhalation of respiratory droplets in indoor environments is one of the significant routes of COVID-19 infection. In many cases, patients are isolated in hospitals and quarantine centers to minimize the spread. However, the rooms allocated to these patients are accessed by health care and sanitization workers a couple of times in a day. Since the expiratory activities release airborne droplets with certain viral load, there is a greater need to study the survival of these droplets in the room of a patient to control the exposure to the accessing people. A bi-compartment and bi-component numerical model is developed to study the survival of these droplets in a room, taking into consideration the deposition rates of the droplets and the ventilation rates in the room. The vital aspects related to the survival of the droplets, such as the effect of the severity of the infection, types of releases, size-dependent deposition and role of ventilation are discussed.